Echo - Block, Francesca Lia. (New York Joanna Cotler Books/HarperCollins, 2001)
Jealous of her perfect mother and ignored by her artist father, Echo seeks attention and healing from a variety of people living in beautiful Los Angeles.
Keywords: Los Angeles (Calif.) -- Fiction